The Exercise and Protection of the Right to a Surviror’s Pension in Extramarital Relations, or what has the legislator failed to disclose? - Obradović, Goran; Tasić, Anđelija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The amendments to the Pension and Disability Insurance Act, enacted at the end of 2019, envisage that the right to a family pension can also be exercised by the surviving extramarital partner. Thus, extramarital partners have been equated (for the first time) with spouses in matrimonial relations. In order to be entitled to a survivor’s pension, both spouses and extramarital partners must inter alia spend at least three years in marriage or extramarital union, or have a child together. The existence of an extramarital union is determined in a non-litigious proceeding. Although this statutory specification of the constitutional norm on the equality of marriage and extramarital union is praiseworthy, the authors point out that the new legal provision raises a number of issues. The situation is indisputable if one man and one woman were in an exclusive extramarital relationship that lasted for a long time, and particularly if they have at least one child together. However, in the event that one of them was in a parallel extramarital union with another person, or if the condition of gender differentiation does not exist or has ceased to exist, it raises the question how the existence of an extramarital union will be proven in non-litigious proceedings. The authors aim to examine whether the existing legal framework provides for achieving the goal of the provision envisaged in the Pension and Disability Insurance Act, and how possible abuses of this right can be prevented in order to protect the conscientious (bona fides) users acting in good faith.